Hubungan Kepemimpinan, Motivasi Kerja dan Kinerja Pegawai (Studi pada Dinas Kimpraswil Provinsi Riau) - Asmara Hendra Komara (Jurnal Aplikasi Manajemen, 2012)
In recent years, academic researchers collected data for emotional intellegence competence that required for leadership. The findings give framework about emotional qualified leadership to inspire, motive desire and enthusiasm, as well as make the people has motivation and commitment. Nowadays, emotional feeling at work place, especially emotional intellegence causes one discuss in organizations. The main task for a leader is to motivate cheerful, optimism, and desire in implementing a job, as well as develop cooperation and confidence. The aim of this research generally is to examine and analyze the effect of leadership, organizational culture, organizational strategy and working motivation of employee performance. Sample is 120 respondents, data collecting with questionairy and interview. Data analysis uses structural equation model with using AMOS 4.01. The result of study shows: 1) Leadership has significant influence on working motivation. 2) Leadership has significant on employee performance. and 3)Working motivation has significant influence on employee performance.Keywords: leadership, working motivation and employee performance